Fall in Vitamin D Levels during Hospitalization in Children. (30th March 2014) - Dayal, Devi; Kumar, Suresh; Sachdeva, Naresh; Kumar, Rakesh; Singh, Meenu; Singhi, Sunit
Abstract : Plasma levels of 25-hydroxyvitamin D [25(OH)D] were measured by competitive Electrochemiluminescence Immunoassay (ECLIA) in 92 children (67 boys, 25 girls) aged 3 months to 12 years at admission to hospital (timepoint 1, T1) and at discharge (timepoint 2, T2). There was a significant fall in the mean 25(OH)D from T1 (71.87 ± 27.25 nmol/L) to T2 (49.03 ± 22.25 nmol/L) (mean change = 22.84 nmol/L, P value = 0.0004). Proportion of patients having VDD (levels <50 nmol/L) at admission (25%, 23/92) increased significantly at the time of discharge (51.09%, 47/92) (P = 0.0004 ). There was a trend towards longer duration of hospital stay, requirement of ventilation and inotropes, development of healthcare-associated infection, and mortality in vitamin D deficient as compared to nondeficient patients though the difference was statistically insignificant. In conclusion, vitamin D levels fall significantly and should be monitored during hospital stay in children. Large clinical studies are needed to prospectively evaluate the effect of vitamin D supplementation in vitamin D deficient hospitalized children on various disease outcome parameters.